Characterization of a novel cyfluthrin-degrading bacterial strain Brevibacterium aureum and its biochemical degradation pathway - Chen, Shaohua; Dong, Yi Hu; Chang, Changqing; Deng, Yinyue; Zhang, Xi Fen; Zhong, Guohua; Song, Haiwei; Hu, Meiying; Zhang, Lian-Hui (Bioresource technology, 2013)
► A new bacterium Brevibacterium aureum was isolated and characterized. ► It utilizes cyfluthrin as a growth substrate and degrades high concentrations. ► The bacterium was able to degrade a wide range of other pyrethroid insecticides. ► A novel degradation pathway for cyfluthrin was proposed based on the metabolites. ► The bacterium harbors the metabolic pathway for the detoxification of cyfluthrin. Brevibacterium aureum DG-12, a new bacterial strain isolated from active sludge, was able to degrade and utilize cyfluthrin as a growth substrate in the mineral medium. Response surface methodology using central composite rotatable design of cultural conditions was successfully employed for optimization resulting in 88.6% degradation of cyfluthrin (50mgL−1) within 5days. The bacterium degraded cyfluthrin by cleavage of both the carboxylester linkage and diaryl bond to form 2,2,3,3-tetramethyl-cyclopropanemethanol, 4-fluoro-3-phenexy-benzoic acid, 3,5-dimethoxy phenol, and phenol, and subsequently transformed these compounds with a maximum specific degradation rate, half-saturation constant and inhibition constant of 1.0384day−1, 20.4967mgL−1, and 141.9013mgL−1, respectively. A novel degradation pathway for cyfluthrin was proposed based on analysis of these metabolites. In addition, this strain was found capable of degrading a wide range of synthetic pyrethroid insecticides. Our results suggest that B. aureum DG-12 may be an ideal microorganism for bioremediation of the pyrethroid-contaminated environments.